2011
DOI: 10.1007/s00421-011-2071-4
|View full text |Cite
|
Sign up to set email alerts
|

Energy demands in taekwondo athletes during combat simulation

Abstract: The purpose of this study was to investigate energy system contributions and energy costs in combat situations. The sample consisted of 10 male taekwondo athletes (age: 21 ± 6 years old; height: 176.2 ± 5.3 cm; body mass: 67.2 ± 8.9 kg) who compete at the national or international level. To estimate the energy contributions, and total energy cost of the fights, athletes performed a simulated competition consisting of three 2 min rounds with a 1 min recovery between each round. The combats were filmed to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
187
3
29

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(241 citation statements)
references
References 25 publications
19
187
3
29
Order By: Relevance
“…Each specific combat sport has a unique combination of rules that confers singular characteristics to each one (e.g., grappling-based techniques or striking-based techniques; scoring system; number of rounds; recovery time between rounds; time duration of each round; distribution of gender; organization in weight divisions) (Poceco, Ruedl, Stankovic et al, 2013;Harmer, 2010). Despite those differences, studies have shown that most combat sports can be characterized as high-intensity, intermittent sports (Campos, Bertuzzi, Dourado, et al, 2012;Artioli, Gualano, Franchini et al, 2009;Franchini, Del Vecchio, Matsushigue et al, 2011;Terbizan & Selievold, 1996;Del Vecchio, Hirata, & Franchini, 2011). Consequently, injury risk had been consistently high in these athletes (Kobayashi, Kanamura, Koshida et al, 2010), even if the International Olympic Committee initiated and developed the injury and illness surveillance system during the 2008 Beijing and 2012 London Olympics (Junge, Engebretsen, Mountjoy et al, 2009;Engebresten, Soligard, Steffen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Each specific combat sport has a unique combination of rules that confers singular characteristics to each one (e.g., grappling-based techniques or striking-based techniques; scoring system; number of rounds; recovery time between rounds; time duration of each round; distribution of gender; organization in weight divisions) (Poceco, Ruedl, Stankovic et al, 2013;Harmer, 2010). Despite those differences, studies have shown that most combat sports can be characterized as high-intensity, intermittent sports (Campos, Bertuzzi, Dourado, et al, 2012;Artioli, Gualano, Franchini et al, 2009;Franchini, Del Vecchio, Matsushigue et al, 2011;Terbizan & Selievold, 1996;Del Vecchio, Hirata, & Franchini, 2011). Consequently, injury risk had been consistently high in these athletes (Kobayashi, Kanamura, Koshida et al, 2010), even if the International Olympic Committee initiated and developed the injury and illness surveillance system during the 2008 Beijing and 2012 London Olympics (Junge, Engebretsen, Mountjoy et al, 2009;Engebresten, Soligard, Steffen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Outra variável relevante para atletas de mmA é o condicionamento aeróbio, que permite aos lutadores: i) manter a intensidade elevada durante todo combate, ii) possuir melhor recuperação e iii) manter a intensidade durante os rounds, principalmente nos seus momentos finais (DEL VECCHIO; HIRATA; BOUNTY et al, 2011;CAmPOS et al, 2012). Indica-se que, no período fora de temporada competitiva, estes lutadores devam realizar de 1 a 2 treinos aeróbios semanais, e durante a temporada competitiva deve ser aumentado para 3 a 5 sessões (RATAmESS, 2011).…”
Section: Discussionunclassified
“…While combat sports have been classified as mixed in terms of its metabolism predominance, some investigations suggested that striking combat sports such as karate and taekwondo present lower glycolytic reliance, high aerobic contribution and the alactic metabolism contributing to the decisive actions performed by the athletes to score (Beneke, Beyer, Jachner, Erasmus, & Hütler, 2004;Campos, Bertuzzi, Dourado, Santos, & Franchini, 2012), while other authors reported data that permit to conclude that grappling combat sports such as Brazilian jiujitsu, judo and wrestling rely more on the glycolytic pathways when compared to striking combat sports (Andreato et al, 2012;Franchini, Artioli, & Brito, 2013;Yoon, 2002). Additionally, some investigations have presented evidence that athletes with different fighting styles presented different physiological response to the match (Franchini, Takito, & Bertuzzi, 2005) and different long-term markers of aerobic and anaerobic metabolisms (Gariod, Favre-Juvin, Novel, Reutenauer, Majean, & Rossi, 1995).…”
Section: Candidate Genes and Combat Sportsmentioning
confidence: 99%